PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN (Studi Kasus Pada Service dan Spare Part Mobil PT. Nusantara Berlian Motor Pekanbaru) - Anom Dwi Wahyuni; Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine the effect of service quality and product quality on customer satisfaction of service and spare part PT. Nusantara Berlian Motor Pekanbaru partially and simultaneously. This study uses questionnaires as a means of collecting data distributed to 100 customers of service and spare part PT. Nusantara Berlian Motor Pekanbaru. Data from the questionnaire was further processed using descriptive analysis and statistical analysis using SPSS 25.0 by performing validity test, reliability test, simple linear regression analysis, multiple linear analysis, coefficient of determination analysis, and hypothesis test consisting of t test (partial) and F test (simultaneous). This result showed that the result of the first hypothesis testing is service quality to customer satisfaction showed t count (9,949) > t table (1,984), it means service quality significantly influence customer satisfaction. The result of second hypothesis testing is product quality to customer satisfaction show t count (7,746) > t table (1,984), it means product quality have significant effect to customer satisfaction. The result of the third hypothesis testing, namely service quality and product quality on customer satisfaction show F count (59,844) > F table (3,09), it means service quality and product quality have significant effect to customer satisfaction. Keywords: Service Quality, Product Quality, Customer Satisfaction